A textbook of environmental studies - Dawan, Ashok (Saurabh, 2012)
This textbook on environmental studies has been written for students, teachers and all who are interested in environmental science. It covers the entire breadth of the environmental studies, providing concise, non-technical explanations of physical processes and systems and the effect of human activities. It explores the interactions of humans within the natural environment and probes issues thoroughly examining their scientific basis, their history, and society's response. It is hoped that the contents of the book will enable readers to critically evaluate the latest environmental issues and to apply that understanding to situations and events in their everyday lives.--Provided by publisher.